2022
DOI: 10.1136/jclinpath-2021-208035
|View full text |Cite
|
Sign up to set email alerts
|

GATA3 positivity is associated with poor prognosis in patients with oesophageal squamous cell carcinoma

Abstract: AimsGATA-binding protein 3 (GATA3) is a zinc finger transcription factor with diverse biological functions and is an excellent diagnostic marker for breast and urothelial carcinoma. We aimed to study GATA3 expression in oesophageal squamous cell carcinoma (SCC) and its significance with respect to histological features, clinical parameters and overall survival.MethodsWe characterised GATA3 immunohistochemistry in 40 patients with oesophageal SCC. Electronic medical records were reviewed for clinical and follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…These transcription factors act as tumor suppressors in some cancers [72][73][74][75]. However, consistent with results of the present study, their activities promote aggressive behavior in other cancers, including those of mesenchymal origin [76][77][78][79]. Our results are therefore consistent with those reported in many previous studies, most of which have been conducted on human tumors, and underscore commonalities in mechanisms responsible for tumorigenesis and cancer behavior in both species.…”
Section: Discussionsupporting
confidence: 93%
“…These transcription factors act as tumor suppressors in some cancers [72][73][74][75]. However, consistent with results of the present study, their activities promote aggressive behavior in other cancers, including those of mesenchymal origin [76][77][78][79]. Our results are therefore consistent with those reported in many previous studies, most of which have been conducted on human tumors, and underscore commonalities in mechanisms responsible for tumorigenesis and cancer behavior in both species.…”
Section: Discussionsupporting
confidence: 93%
“…In another study, Chi et al [21] detected GATA3 immunopositivity in 28% of the esophageal SCC cases studied; the survival rate was lower in these cases compared to patients who did not exhibit immunoreactivity. The authors concluded that GATA3 positivity was associated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 87%
“…36 The expression of GATA3 in SCCs appears to vary by anatomic site and by analysis, with cutaneous SCCs reportedly being variably positive, 10 and noncutaneous SCCs, including cervical, laryngeal, and pulmonary SCCs displaying much less frequent GATA3 expression. 1,10,[35][36][37] A prognostic role may be emerging for GATA3 expression in SCCs at some sites: Chi et al 9 recently reported that GATA3 expression is associated with poor prognosis in esophageal SCC. Furthermore, GATA3 appears to be mechanistically involved in squamous cell carcinogenesis and/or progression at various sites.…”
Section: Discussionmentioning
confidence: 99%
“…7 Conversely, the expression of GATA3 has been associated with worse prognosis in soft tissue tumors, 8 and esophageal squamous cell carcinoma (SCC). 9 Among the skin and associated cutaneous structures, the epidermis, sebaceous glands, hair shafts, eccrine, and apocrine sweat glands express GATA3 protein, and many neoplasms, particularly basal cell carcinoma and SCC can be immunoreactive for GATA3, 1,10 although the reported frequencies of expression have varied significantly. Not much is known about GATA3 expression patterns in vulvar squamous cell carcinoma (VSCC).…”
mentioning
confidence: 99%
See 1 more Smart Citation